2012 Ibrahim Index of African Governance Summary - Mo Ibrahim Foundation (Swindon Mo Ibrahim Foundation, 2012)
The 2012 IIAG confirms that governance progress has been achieved since 2000. There have been positive trends in 11 out of the 14 sub-categories, including all sub-categories within the Sustainable Economic Opportunity and Human Development categories. The other categories, Safety & Rule of Law and Participation & Human Rights have registered declines. However improvements were seen in the sub-categories National Security and Gender. Interestingly, at the indicator level, the most progress appears in Cross-Border Tensions, Core International Human Rights Conventions, Legislation on Violence against Women, Ratio of External Debt Service to Exports, Digital Connectivity and Anti-Retroviral Treatment Provision. The largest declines have been registered in Workers? Rights, Safety of the Person and Transfers of Power. It is encouraging to note that the Millennium Development Goals have undoubtedly contributed to the improvement of the Human Development category. The post-MDG framework now has the potential to make similar improvements across the full package of expected goods and services that citizens have the right to expect.
Keywords: Governance, Human Rights Human Development Sustainable Economic Opportunity